2006
DOI: 10.2166/wst.2006.041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient loads from a mountain forest including storm runoff loads

Abstract: Water quality and flow rates at a weir installed on the end of Aburahi-S Experimental Watershed (3.34 ha) were measured once a week from 2001 to 2003 and in appropriate intervals from 30 min to 6 h during five storm runoff events caused by each rainfall from 8 mm to 417 mm. The average annual loads of total nitrogen (TN) and total phosphorus (TP) were calculated to be 19.0 and 0.339 kg ha(-1) y(-1) from the periodical data by using the integration interval-loads method (ILM), which did not properly account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…method was developed in order to evaluate storm-runoff loads by using precipitations in cases of limited data of concentrations and flow-rates Kunimatsu et al, 2006). L(R)-equations were derived from the correlation between the storm-runoff load L Si and corresponding rainfall depth R i measured during the storm runoff event i.…”
Section: L(r) Methods L(r)mentioning
confidence: 99%
“…method was developed in order to evaluate storm-runoff loads by using precipitations in cases of limited data of concentrations and flow-rates Kunimatsu et al, 2006). L(R)-equations were derived from the correlation between the storm-runoff load L Si and corresponding rainfall depth R i measured during the storm runoff event i.…”
Section: L(r) Methods L(r)mentioning
confidence: 99%
“…This equation is called the L-Q equation model (e.g., Komai et al, 2003;Kunimatsu et al, 2006) and shows the relationships between nutrient load (L) and water discharge (Q). We decided the optimum coefficients (a and n) of two sets (Cases 3 and 4) by applying the least-squares method to antilogarithmic and logarithmic regression curves.…”
Section: Estimations In 4 Cases Of Nutrient Loadsmentioning
confidence: 99%
“…The results of our evaluation by weekly field research and the automatic water level records showed that the Case 2 evaluation gave a higher discharge than in Case 1. Kunimatsu et al (2006) calculated cv (coefficient of variation) values of the annual loads in Mano River (watershed area of 16.4 km 2 ), under various conditions of observation frequency (from every day to every 30 days) by the same method as Case 2 of our study. Kunimatsu et al (2006) also reported the cv values of the annual loads calculated from the data of weekly (7-days interval) observation were 0.54 for total nitrogen and 0.74 for total phosphorus, and that of discharge was 0.23.…”
Section: Load Estimationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of concentration and catchment outflow is an appropriate method for calculating fluxes of dissolved matter, as shown by the Cl-balance (Table 1). However, in the context of a Japanese catchment adjacent to Kutsuki, this approach may overestimate TN and TP fluxes due to the strong variability of particulate matter during rain runoff events (Kunimatsu et al, 2006a). In particular, suspended particulate matter (SM), PN and PP are highly sensitive to particulate matter variability.…”
Section: Overviewmentioning
confidence: 99%